Characterization of scallop midgut gland certified reference material for quantification of diarrhetic shellfish toxins. (15th November 2019) - Yarita, Takashi; Inagaki, Shinsuke; Miyamoto, Ayano; Yamazaki, Taichi; Kawaguchi, Migaku; Uchida, Hajime; Takatsu, Akiko; Suzuki, Toshiyuki
Highlights: Scallop midgut gland certified reference material was characterized by co-laboratory study. Homogenous and stable naturally contaminated scallops were spiked with okadaic acid. LC–MS/MS based on standard addition method using SI-traceable standard-spiking solution was used. Certified values with expanded uncertainties were found for okadaic acid and dinophysistoxin-1. Abstract: A scallop midgut gland certified reference material, NMIJ CRM 7520-a, was developed for validation and quality assurance during the inspection of shellfish for diarrhetic shellfish toxins. The candidate material was prepared by using naturally-toxic and nontoxic boiled midgut glands spiked with okadaic acid (OA). The homogeneity and stability of the material were found to be appropriate. For the characterization of OA and dinophysistoxin-1 (DTX1), nine participants were involved in a co-laboratory study based on the Japanese Official Testing Method, where the compounds were assayed by liquid chromatography-tandem mass spectrometry following alkaline hydrolysis. The analytical values were obtained by the standard addition method with a standard spiking solution calibrated using the standard-solution certified reference materials OA and DTX1. The certified concentrations with expanded uncertainties (coverage factor k = 2, approximate 95% confidence interval) were determined to be (0.205 ± 0.061) mg/kg for OA and (0.45 ± 0.11) mg/kg for DTX1.